Vice-Chancellor visits China - UMP, PNC
Universiti Malaysia Pahang (UMP) forged ties with Hebei University (HBU) and Hebei University Science and Technology (HEBUST) in a move to strengthen programmes in academic, international and mobility involving students and staff of UMP.